A review on agency cost of shariah governance in mutual fund - Mohd Fikri, Sofi; Yahya, Mohamed Hisham; Chowdury, Taufiq Hassan Shah (EconJournals, 2017)
Mutual fund has become an increasingly important investment vehicle for retail investors, especially among households. Besides developing the institutional investment as an efficient momentum trader, the long-established separation of ownership and control in contemporary type of fund management has very much caused depreciation in shareholder value under minimum investor protection environment. The unobserved activities and widely magnitude decision skills of managers under imperfect contract with the tendency to serve self-interest exacerbates the shareholder wealth, predominantly in Shariah mutual fund (SMF), pertaining to dual investing interests. This paper reviews the theoretical and empirical literature with central attention given to the existing governance structure, Shariah governance in religious based fund, and some other related internal governance mechanisms. Concurrently, the review explains theoretically and conceptually the interrelationships among all relevant governance mechanisms. After some rigorous discussion and argument, this paper recommends further empirical investigation into this line of research to integrate the gap from developed market evidence.